Penggunaan iPad Mendukung Pembelajaran pada Mahasiswa iLearning - Rano Kurniawan; Henderi Henderi; Fitria Nursetianingsih (CCIT Journal, 2012)
Development of science and technology has a fast movement. Development of technology is characterized by an increase in capacity of new innovations in science and technology, and providing a broad impact on a whole life. So, many things didn't escape the using of technology. Various innovation related to technological development are constantly emerging. Various parties trying to take control and develop the technology by conducting research and development activities. In the world of education, teaching methods is growing. Not only seen from the performance index, but it needed a good implementation in the field. Ability, means of support and ideas is a package that can not be separated in the development of science and technology. The term e-learning (electronic learning) in education. E-learning is a basic and logical consequence of the development of information and communication technology. E-learning can be defined as a distance learning based internet. E-learning has to do with i-learning but the two words have different senses. iLearning (integrated learning) can be interpreted as a method of learning who balance among the brain, movement, and intelligence. iLearning has related with 4B (Learn, Work, Play, and Pray). iLearning with the supports can be carried out effectively and efficiently